2006
DOI: 10.1158/1078-0432.ccr-06-0134
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Identification of UCA1 as a Very Sensitive and Specific Unique Marker for Human Bladder Carcinoma

Abstract: Purpose: The most common genitourinary malignancy in China is bladder transitional cell carcinoma (TCC). Early diagnosis of new and recurrent bladder cancers, followed by timely treatment, will help decrease mortality. There are currently no satisfactory markers for bladder cancer available in clinics. Better diagnostic methods are highly demanded. Experimental Design: In this research, we have used comprehensive expressed sequence tag analysis, serial analysis of gene expression, and microarray analysis and q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
359
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 421 publications
(373 citation statements)
references
References 26 publications
4
359
2
Order By: Relevance
“…Detection of PCA3 in the urine has been shown to be a more specific diagnostic marker in prostate cancer than the other commonly used prostate-specific antigen (Lee et al 2011). UCA1 (urothelial carcinoma associated 1) transcript detected in urine has been demonstrated to be a sensitive biomarker for bladder carcinoma (Wang et al 2006). HULC is posed as a promising diagnostic biomarker for hepatocellular carcinoma since it has been detected with high frequency in the plasma of HCC patients (Xie et al 2013).…”
Section: Lncrnas: Diagnostic Markers In Thyroid Cancermentioning
confidence: 99%
“…Detection of PCA3 in the urine has been shown to be a more specific diagnostic marker in prostate cancer than the other commonly used prostate-specific antigen (Lee et al 2011). UCA1 (urothelial carcinoma associated 1) transcript detected in urine has been demonstrated to be a sensitive biomarker for bladder carcinoma (Wang et al 2006). HULC is posed as a promising diagnostic biomarker for hepatocellular carcinoma since it has been detected with high frequency in the plasma of HCC patients (Xie et al 2013).…”
Section: Lncrnas: Diagnostic Markers In Thyroid Cancermentioning
confidence: 99%
“…To further verify this result, we performed RNA immunoprecipitation (RIP) analysis with anti-UHRF1 antibody using lysates from HCT116 cells. qRT-PCR analysis of the immunoprecipitates revealed that UHRF1 was associated with endogenous UPAT, but not with GAPDH mRNA, U1 small nuclear RNA, ASBEL, or urothelial cancer associated 1 (UCA1) (16,17) (Fig. 2B).…”
Section: Significancementioning
confidence: 99%
“…An increasing number of discoveries of misregulated lncRNA expression across numerous cancer types have suggested that aberrant lncRNA expression may be a major contributor to tumourigenesis. Further, lncRNAs may add another layer to cancer research because their potential usefulness as biomarkers (8)(9)(10)(11)(12)(13)(14)(15). Therefore, to fully understand the complex mechanisms underlying carcinogenesis and cancer metastasis, the role of lncRNAs must be considered.…”
Section: Introductionmentioning
confidence: 99%